Adaptabilidade e planejamento de carreira para jovens universitários: um estudo à luz da teoria da construção de carreira - Pegoretti, Bárbara (2021)
Structural changes in production systems to face globalization, as well as the progressive search for competitiveness by economic agents, have led to a drastic redefinition process in the labor market and, consequently, in the structure of careers. This circumstance ends up imposing on young people, the objects of study of this survey, significant barriers to entry into the labor market. This survey aimed to investigate the relationship between career adaptability resources and the career in young graduates of the business course at the Federal University of Espírito Santo, and for that, a qualitative approach was used through in-depth interviews with eleven students from the last periods of the business course at the university in question. For data analysis, the content analysis technique was used. The thematic axes identified in the speeches were: job market, career expectations, career adaptability and career planning. The results are discussed in terms of the relationships established between the thematic axes. Thus, the study reveals that the perception of the labor market interferes with career planning in two ways. In the first, it is verified that the perception of the labor market impacts on career expectations, which in turn, impact on career planning. In the second, it is identified that the perception of the labor market interferes in the relationship between career adaptability resources and career planning, in order to weaken this relationship. It is observed that for these young people the barriers to entry into the labor market are perceived as being so difficult to overcome that carrying out a career planning does not seem to have the desired effect. Thus, young people end up resorting only to adaptability resources to deal with the university-labour market transition. It is identified that due to the upheavals in the dynamic world of work, some young people have developed a feeling of insecurity, for not knowing how to deal with such changes in the working world. The practical implications of this study refer to the role of the university in preparing these young people in relation to career planning and the development of adaptability resources to deal with their entry into the labor market.